2004
DOI: 10.1002/mrd.20213
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenesis in the red crab Charybdis feriatus: Hepatopancreas‐specific expression and farnesoic acid stimulation of vitellogenin gene expression

Abstract: Vitellogenesis in the mature female crab Charybdis feriatus occurs all year round during which active synthesis of the vitellogenin (Vg) precursor occurs. Several polypeptides from the ovaries were shown to be immuno-reactive to the shrimp vitellin (Vn) antibody. N-terminal amino acid sequence determination revealed that several ovarian polypeptides and one polypeptide secreted by the hepatopancreas were identical to part of the C. feriatus Vg (CfVg) precursor. The full-length cDNA sequence encoding a protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 39 publications
4
70
0
Order By: Relevance
“…Additional sequences of LLTPs from arachnids may help define the context of the divergence of M-177. Importantly, the Vtg of decapodan Crustacea is not directly related to the Vtg genes of other taxons, as assumed by others (52)(53)(54)(55)(56)(57)(58)(59)(60), but is an apoB-like LLTP. This observation explains previous phylogenetic analyses on Vtgs only (57,62,69,70), in which decapodan Vtg failed to group with other invertebrate Vtgs.…”
Section: Three Families Of Lltpsmentioning
confidence: 86%
See 1 more Smart Citation
“…Additional sequences of LLTPs from arachnids may help define the context of the divergence of M-177. Importantly, the Vtg of decapodan Crustacea is not directly related to the Vtg genes of other taxons, as assumed by others (52)(53)(54)(55)(56)(57)(58)(59)(60), but is an apoB-like LLTP. This observation explains previous phylogenetic analyses on Vtgs only (57,62,69,70), in which decapodan Vtg failed to group with other invertebrate Vtgs.…”
Section: Three Families Of Lltpsmentioning
confidence: 86%
“…In another class of arthropods, the decapodan Crustacea (e.g., lobster, crayfish, crab, shrimp), two distinct LLTPs have been identified, a CP (7,8) and a yolk protein named Vtg (52)(53)(54)(55)(56)(57)(58)(59)(60). Although both LLTPs have been identified only in distinct species, the relatively close relationship among these species as well as the divergence of the identified proteins strongly suggest that the subset of LLTPs present in decapodan Crustacea con-sists at least of one CP and one Vtg.…”
Section: Lltp Family Membersmentioning
confidence: 99%
“…However, the multiple spatial locations of FA-O-MeT gene expression are an open area of interest to all crustacean sesquiterpenoid researchers. Recently, Mak and colleagues (Mak et al, 2005) demonstrated that FA (low concentrations) can also stimulate Charybdis feriatus Vg gene expression in the HP. Similarly, FA also consistently stimulated MeVg1 expression by the HP explants, while both FA and 20-hydroxyecdysone stimulated ovarian explants of M. ensis in vitro (Tiu et al, 2006).…”
Section: Mfmentioning
confidence: 99%
“…Experimental evidence suggests that major functions of MF in crustaceans are in the positive regulation of the molt cycle and enhancing reproductive maturation [102,104]. Methyl farnesoate has been implicated as a morphogen in postembryonic larval stages of crustacean development [104] and in reproductive maturation in decapods, in which it increases production of vitellogenin and oocytes [104,105]. Methyl farnesoate also stimulates gonadal maturation of both male and female decapods [104,106].…”
Section: Mandibular Organmentioning
confidence: 99%